Dakwah dan Penyelenggaraan Pendidikan Tentang Haji: Strategi Pengembangan Masyarakat Islam Humanis-Religius - Fa'atin, Salmah (Institut Agama Islam Negeri (IAIN) Kudus, 2019)
AbstractThe phenomenon of high enthusiasm for Hajj among Muslim communities is an indicator of the magnitude of the impact and benefits obtained from its implementation. The benefits of Hajj religious-humanists have undergone many shifts to the economic sphere and social status. This is inseparable from the results of people's understanding of the Hajj ritual and its ins and outs. Community understanding is closely related to the results of education and teaching obtained in formal and non-formal education activities. A good strategy is needed to produce an understanding of the Hajj correctly and with quality. This article aims to develop a strategy for developing a humanist-religious Islamic community through holistic education about Hajj. The phenomenon of hajj in society is described and analyzed using descriptive-analytical methods, then studied the development of teaching and developed using holistic education theory. The results show that holistic education about hajj requires an integrative approach in teaching the theme of the Hajj, by understanding the text about Hajj with various approaches to the fields of science, religion, socio-culture, economics and psychology. Multidisciplinary science will provide an understanding of the Hajj as a whole and comprehensively, so that the extinction of Hajj can be manifested in the realm of social life in a real way as the moral ideal of pilgrimage pilgrimage.Keywords: community development, holistic education, teaching strategies